THEORETICAL APPROACHES AND TOOLS OF ESTIMATING THE LIQUIDITY OF FINANCE ASSETS IN PORTFOLIO INVESTMENT TASKS - Daria A. Bystrova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article substantiates the approach to the content and methods of estimating the liquidity of finance assets included in the investor’s portfolio (a professional institutional market participant or non- institutional), gives their comparative analysis embracing both the phenomenon of liquidity and methods of its estimation on the basis of market information. It is proposed to consider an approach based on the use of the extended set of liquidity indices, including urgency, depth and flexibility, density and volume of dealings with assets, especially for emerging finance markets. Multidimensional liquidity estimations allow us to get its more accurate values in comparison with one-dimensional. It actualizes the topic of improving the traditional models and designing more original methods of finance asset liquidity estimation, which is used in criteria and restrictions of portfolio investment models.